Sistem Informasi Desa Siaga Pangan Menghadapi Covid19 berbasis Web Service - Amanda Putri Septiani; Wira Junardi; Ainun Amaliah; Arief Bachtiar; JM Ihza Mahendra; Muhammad Irfan Muttaqin (Jurnal Sistem Cerdas, 2020)
SIDAVID19 is a food alert village information system to deal with COVID19, a capability that must be owned by the system for recording the entry and distribution of staple goods, BKPD can know food supplies and aid recipients in an integrated manner as well as village residents to obtain information to distribute village food via the internet. Information integration is a necessity for the government in realizing integrated services to the public. The SIDAVID19 service is one of the services provided to facilitate the management of the distribution of staple goods during the COVID9 emergency and access to information for the public and BKPD. This study describes the design of the SiDavid19 service, which is a web service technology to connect users and providers in retrieving information needed by users.